Analisis Kualitas Aparatur Sipil Negara dalam Meningkatkan Pelayanan Publik Di Masa Pandemi - Daniel Marshal Sajou (Jurnal Syntax Transformation, 2022)
State Civil Apparatus Employees carry out their duties and obligations in providing public services based on Article 11 and 23 of the Law of the Republic of Indonesia Number 5 of 2014 concerning the State Civil Apparatus so a good public service system is needed so that every State Civil Apparatus (ASN). However, it is not only a good public service system but also the professionalism of ASN employees which is then reflected in the implementation of public services in the community. During the pandemic, several things need to be developed and considered, especially the change from offline habits to now being required to carry out their duties and functions online, and supported by the plan of President Jokowi to replace ASN with artificial intelligence (AI). The results of the study indicate that a clear division of authority is not enough, so it is necessary to develop a new paradigm for ASN to improve the competence of the ASN itself. This study aims to show that State Civil Apparatus Employees must make changes and adjustments during the pandemic related to increasing managerial and information technology abilities and decision making.